A Model For Teaching Arabic Grammar In Light Of The Common European Framework Of Reference For Languages - Mohamed Ahmed Abdalla, Erfan Abdeldaim (Ijaz Arabi Journal of Arabic Learning, 2024)
With its intricate arrangement, classification, abundance, and bifurcation, Arabic grammar presents challenges for learners rooted in historical contextual factors and pedagogical approaches. This study addresses the need for a comprehensive examination and categorization of Arabic grammatical rules based on specific criteria aligned with the Common European Framework of Reference for Languages (CEFR). It aims to identify prevalent and obscure rules, offering a compilation organized according to CEFR standards. The objective is to streamline Arabic language acquisition by reducing the overwhelming quantity of rules presented in textbooks for non-native speakers. The primary obstacle learners face is the complex nature of Arabic grammar, compounded by inadequate organization and delivery of existing materials. This leads to a skewed focus on less practical rules, hindering everyday speech and writing proficiency. Statistical analyses reveal the need for restructuring instructional sequences to prioritize commonly used rules. The proposal advocates aligning grammatical structures with CEFR guidelines and incorporating essential structures for non-Arabic speakers, promoting a modern and coherent language. By addressing these issues, this study motivates learners and bridges the gap between non-native and native proficiency levels in Arabic. The research relied on older references for the theoretical framework due to the need for more specialized references on teaching Arabic grammar to non-native speakers.